Creative imagery discoveries and inventions in visualization - Finke, Ronald A. (L. Erlbaum Associates, 1990)
Bringing together the results of experiments on discovery and invention in visualization conducted by the author over a three year period, this book reports new findings on the generation of creative inventions and concepts using mental imagery, and proposes a reconceptualization of the creative process. Creative Imageryintroduces the concept of ?preinventive forms? and describes an approach to creative invention differing from those typically used in problem-solving studies. There are two unique features of this book. First, it combines the experimental methods of cognitive science with the opportunity to explore and discover creative inventions in imagination. Second, it provides readers with numerous opportunities to use the creative imagery techniques to develop their own inventions and conceptual discoveries. This text is of particular interest to scientists working in the fields of experimental psychology, cognitive psychology, and cognitive science. The techniques for generating creative inventions will also be of interest to people working in engineering, architectural design, and the visual arts.